PENGARUH CELEBRITY ENDORSEMENT DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINYAK GORENG KEDELAI MISOYA DI PT. SARI SARANA KIMIATAMA MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA MASA PANDEMI COVID-19 - Kevin Renaldo Teguh (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
With the development of technology, there are many ways to do advertising. Some ways that can be done are celebrity endorsement and promotion. The research has a purpose to determine the significant effect of celebrity endorsement and promotion on purchase decisions and to see the effect of celebrity endorsement and promotion on purchase intention. Analyze purchase intention as mediation to purchase decision. The research population were the customers Misoya cooking oil at PT. Sari Sarana Kimiatama. Sampling was taken by non-probability sampling with purposive sampling method. The sample taken in this study were 80 respondents. The analysis method was carried out quantitatively using SPSS software version 25 and SMART PLS. Sampling used an online questionnaire and the scale was used with a Likert scale. The results of the study found that there was a significant influence between the celebrity endorsement and promotion variables on buying interest. Promotion variables have a positive and significant effect on purchase decisions. The celebrity endorsement variable has no significant effect on purchasing decisions. In this study, buying interest can be a mediation for the celebrity endorsement variable to the purchase decision but does not mediate the promotion to the purchase decision.